The Heparin-Mobilisable Pool of Platelet Factor 4: A Comparison of Intravenous and Subcutaneous Heparin and Kabi Heparin Fragment 2165 - O’Brien, J R; Etherington, M D; Pashley, Michelle A (Thrombosis and Haemostasis, 1985)
Some clinical advantages are claimed for low molecular weight heparin so the mobilisation of platelet factor 4 (PF 4) from the endothelial pool by the heparins may be relevant. Unfractionated (UF) heparin has been compared with Kabi heparin fragment 2165. A single intravenous (i. v.) injection of 60 iu/kg heparin was compared with 5000 anti-Xa units of Kabi-2165. Less PF 4 was mobilised by Kabi-2165 and some apparently remained in the pool and was released when the pool was subsequently challenged by giving i.v. heparin. Subcutaneous (s. c.) injections of 5000 iu heparin twice daily were compared with 5000 anti-Xa units of Kabi-2165 once daily, each given for a week. The plasma PF 4 was never raised yet when finally challenged with i.v. heparin the pool was “empty” or refractory after the s.c. heparin but some PF 4 remained after the s.c. Kabi-2165. The two glycosaminogly-cans (GAGs) had widely differing half-lives but the t/2 of the PF 4 mobilised by the two GAGs was similar even though the PF 4 is apparently bound to the GAG.
Keywords: Heparin; Kabi-2165; Plasma PF4; Heparin-mobilisable pool of PF4